2014
DOI: 10.1590/1982-021620145113
|View full text |Cite
|
Sign up to set email alerts
|

Análise da força de mordida nos diferentes tipos de maloclusões dentárias, segundo Angle

Abstract: OBJETIVO:analisar a máxima força de mordida na oclusão normal e maloclusões de Angle; observar a frequência de ocorrência dos tipos de oclusões; analisar a existência de diferença entre as medidas desta força e relacionar a força de mordida com índice de massa corpórea (IMC) de cada indivíduo.MÉTODOS: a amostra foi composta por 100 estudantes do curso de Fonoaudiologia, com faixas etárias entre 17 e 25 anos. Cada indivíduo realizou: 1) Anamnese: composta por dados de identificação pessoal, informações sobre al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
3
9
0
Order By: Relevance
“…In contrast to the current study, Sathyanarayana et al 14 found that the sagittal morphology does not significantly affect the MVMBF value; consistent with the current study, however, they found a significant correlation with the vertical morphology. In agreement with the current study, de Ara ujo et al 15 also found that the type of occlusion influenced the MVMBF. The authors reported that the number of occlusal contacts determined the chewing efficiency and that chewing was less efficient in patients with malocclusion than normal occlusion.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In contrast to the current study, Sathyanarayana et al 14 found that the sagittal morphology does not significantly affect the MVMBF value; consistent with the current study, however, they found a significant correlation with the vertical morphology. In agreement with the current study, de Ara ujo et al 15 also found that the type of occlusion influenced the MVMBF. The authors reported that the number of occlusal contacts determined the chewing efficiency and that chewing was less efficient in patients with malocclusion than normal occlusion.…”
Section: Discussionsupporting
confidence: 93%
“…According to these values, the calculated Cohen's d and effect-size r were 0.887 and 0.405, respectively. 15 The software used in that study was G*Power software version 3.0.10 with power of 80%, a of 0.05, and effect size (d) of 0.4. 15 The total sample in the present cross-sectional study was determined to be 102.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement of maximum isometric bite force (MIBF) can be performed by using an electronic dynamometer that is useful for evaluating the performance of the muscles of mastication. Several studies have investigated the bite force in different ways, analyzing their relationship with facial morphology, mastication performance, different malocclusions, teething stages and their variability in different populatio ns (3,12,13,14,15,16,17,18,19,20,21) . In order to masticate effectively, the stomatognathic system depends on the muscles of mastication and the craniofacial development pattern, making it essential to investigate the influence of mouth breathing on the bite force in children undergoing craniofacial development.…”
Section: Introductionmentioning
confidence: 99%